2013
DOI: 10.1002/jctb.4130
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bisphenol A and 4‐n‐nonylphenol coupled to nitrate reduction using acclimated activated sludge under anaerobic conditions

Abstract: BACKGROUND: Bisphenol A (BPA) and 4-n-nonylphenol (4-n-NP) are of significant research interest due to their extensive use and toxicological properties. Batch experiments were conducted to investigate the sorption and degradation behavior of BPA and 4-n-NP using acclimated activated sludge either under anoxic conditions in the presence of nitrate or under anaerobic conditions in the absence of nitrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Lu et al [97] suggested a more efficient removal of NPEOs by denitrifying activated sludge, rather than by anaerobic activated sludge. Regarding NP, H. Zhou et al [98] observed an approximately 82% reduction in NP within 8 h. Whereas, Wang et al [95] reported a removal of 89% after 120 h. The authors demonstrated a rise in removal efficacy at an increased nitrate concentration, where the most suitable COD/nitrate ratio was of 15:1. It may imply that the degradation of NP is also facilitated by denitrification.…”
Section: Removal By Anoxic Processesmentioning
confidence: 98%
See 1 more Smart Citation
“…Lu et al [97] suggested a more efficient removal of NPEOs by denitrifying activated sludge, rather than by anaerobic activated sludge. Regarding NP, H. Zhou et al [98] observed an approximately 82% reduction in NP within 8 h. Whereas, Wang et al [95] reported a removal of 89% after 120 h. The authors demonstrated a rise in removal efficacy at an increased nitrate concentration, where the most suitable COD/nitrate ratio was of 15:1. It may imply that the degradation of NP is also facilitated by denitrification.…”
Section: Removal By Anoxic Processesmentioning
confidence: 98%
“…Diverse potencies have been documented probably because the biotransformation of NP in anaerobic conditions may strictly rely on the availability of nitrate in wastewater as an electron acceptor [94]. Indeed, the study of Wang et al [95] revealed that NP was mainly removed via sorption on sludge, and no biodegradation was observed under anaerobic-without-nitrate conditions, suggesting the dominant role of nitrate in NP removal via anaerobic processes. …”
Section: Removal By Anaerobic Processesmentioning
confidence: 99%
“…Several technologies, such as coagulation/flocculation/sedimentation/filtration [ 17 , 18 ], carbon nanomaterials (CNMs) (e.g., carbon nanotubes (CNTs) [ 19 ] and graphene oxides (GOs) [ 20 ]), membrane filtration [ 21 , 22 ], ultraviolet (UV) irradiation [ 23 , 24 ], biological processes [ 25 , 26 ], and advanced oxidation techniques [ 27 , 28 , 29 , 30 , 31 ] have been studied for BPA removal. Nevertheless, energy consumption, low process efficiency, production of toxic by-products, and addition of hazardous chemicals prevent the wider application of all these technologies at large-scale.…”
Section: Introductionmentioning
confidence: 99%
“…EDCs constitute a wide kind of natural and synthetic chemicals, which interfere with the normal behaviour of the endocrine system . Within EDCs, the alkylphenols (APs) are known for their riskiness and common presence in wastewater effluents, since they are components of detergent formulations. One of the most common APs is Triton X‐100 (C 14 H 22 O(C 2 H 4 O) n ).…”
Section: Introductionmentioning
confidence: 99%